Utility of an automated notification system for recruitment of research subjects. Issue 10 (1st June 2010) - Cardozo, Eden; Meurer, William J; Smith, Barbara L; Holschen, Jolie C
Abstract : Background: Experience with a novel method of notifying investigators about research subjects in a university-based emergency department (ED) is reported. Methods: An automated paging system was linked to the electronic medical record to identify inclusion criteria and notify investigators at the time of ED triage. The rate of study enrolment 2 months before and after implementation of the automated system was compared and the time from triage completion to investigator notification was assessed. Results: During the first 2-month period, 1/17 eligible patients were identified by staff. During the second 2-month period, 1/7 eligible patients were identified by staff while the automated paging system recognised 7/7 eligible patients, an absolute increase of 94.5%. The median time from completion of triage to automated notification of investigators was 0 min. Conclusion: Automated paging using the electronic medical record has the potential to improve enrolment in clinical research studies by improving the speed and sensitivity of identifying eligible subjects.